Persons with disabilities in institutions as victims of discrimination and human rights violations - Janjić Biljana; Beker Kosana (Temida, 2016)
The paper describes the position of persons with disabilities in residential institutions in Serbia, with particular focus on the position of women. Our goal is to determine some of the reasons for human rights violations and discrimination against persons with disabilities in institutions through understanding the historical context and attitudes towards them, and to understand the extent to which international human rights framework impacts the improvement of their position. Results of analyses show that adoption of the international and national legal framework grounded in the theory of social model is a necessary but not sufficient condition for de facto equality, because of the rooted negative attitudes towards rights, possibilities, and needs of persons with disabilities that nurture justifications and excuses for multiple deprivations and discrimination. The change of the paradigm and improvement of the position of persons with disabilities requires awareness-raising of the social protection system with the aim of overcoming prejudices and changing practices.